ASSESSING NUTRITIONAL STATUS OF CRITICALLY ILL PATIENTS USING SERUM PREALBUMIN LEVELS - Arbab, Khushbakht; Majid, Hafsa; Jafri, Lena; Akram, Bushra; Raheem, Ahmed; Jamil, Bushra; Hashmi, Madiha; Khan, Aysha Habib (Journal of Ayub Medical College Abbottabad, 2019)
Background: Malnutrition in hospitalized patients, contributes to poor outcomes. Biomarker serum prealbumin, can prevent the complications by commencement of nutritional support to improve clinical outcomes. This study was designed to assess the association between low serum prealbumin level (<18 mg/dl), with length of stay and all cause intensive care unit mortality. Methods: This cross-sectional study was conducted from July 2016 to July 2017 at Aga Khan University Hospital Karachi Pakistan. All consecutive patients, aged between 18 to 70 years, admitted in medical or surgical intensive care unit were included. Demographic, clinical history and blood samples for analysing serum prealbumin were obtained on first day of admission. Patients were categorized into two groups based on their serum prealbumin level (taking <18 mg/dl as low). Results: A total of 139 patients were included in this study; 95 (68.3%) were male. Median (Q3-Q1) prealbumin level of 12.3 mg/dl (18.8-8.7) was observed with low prealbumin level (<18 mg/dl) in 100 (71.9%) patients. All-cause mortality was observed in 26 (26.0%) patients, mortality rate was significantly higher in patients with low prealbumin level (26.0% vs. 17.9%), p-value =0.31). Hospital and intensive care unit length of stay were statistically insignificantly different between the two groups with p-values of 0.27 and 0.44 respectively. Conclusion: We did not find association of low serum prealbumin with length of stay and mortality. Further research is warranted for the assessment of prealbumin as independent predictor of ICU mortality. Keywords: Prealbumin; length of stay; mortality; intensive care unit